2010
DOI: 10.3945/jn.109.109314
|View full text |Cite
|
Sign up to set email alerts
|

Coffee Consumption and Mortality Due to All Causes, Cardiovascular Disease, and Cancer in Japanese Women

Abstract: Coffee contains various compounds that have recently been reported to exert beneficial health effects. However, the conclusion of its relation with mortality has not yet been reached. In this study, we aimed to investigate the associations between coffee consumption and all-cause and cause-specific mortality in Japan. We included 37,742 participants (18,287 men and 19,455 women) aged 40-64 y without a history of cancer, myocardial infarction, or stroke at baseline in our analysis, based on the Miyagi Cohort St… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

7
73
0
3

Year Published

2012
2012
2019
2019

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 90 publications
(85 citation statements)
references
References 18 publications
7
73
0
3
Order By: Relevance
“…Finally, seventeen eligible studies consisting of 1 054 571 participants and 131 212 death events due to all causes were identified and included in the present study (4)(5)(6)8,(22)(23)(24)(25)(26)(27)(28)(29)(30)(31)(32)(33)(34) . The mean follow-up time of each study ranged from 7·1 to 25 years with a median of 15 years.…”
Section: Resultsmentioning
confidence: 99%
“…Finally, seventeen eligible studies consisting of 1 054 571 participants and 131 212 death events due to all causes were identified and included in the present study (4)(5)(6)8,(22)(23)(24)(25)(26)(27)(28)(29)(30)(31)(32)(33)(34) . The mean follow-up time of each study ranged from 7·1 to 25 years with a median of 15 years.…”
Section: Resultsmentioning
confidence: 99%
“…Recent reports indicated that leptin, a secretory product of adipocytes, also present in abnormally high levels in the plasma of obese people, promotes mitosis and suppresses apoptosis in colonic epithelial cells (34) . Moderate coffee consumption has been associated with reduced risk for CRC in some case-control studies (13)(14)(15) , whereas cohort studies showed inconsistent results; animal studies on the effects of coffee constituents, such as caffeine, kahweol and cafestol, on colon tumorigenesis have also shown conflicting results. Based on these data Table 3 Results from logistic regression analyses that evaluated the association of the modified-MedDietScore with colorectal cancer (CRC) in a sample of CRC cases (n 250) and controls group-matched for age and sex (n 250), Athens, Greece, December we decided to assign the greater value (most protective effect) to moderate coffee consumption of 2-3 cups/d (35) .…”
Section: Discussionmentioning
confidence: 98%
“…However, some dietary behaviours, like drinking coffee, adding salt at the table, salted foods, meal frequency and cooking procedures, have not been included in dietary patterns, although they have been associated with the development of chronic diseases, like cancer. Specifically, epidemiological studies have shown that high intake of calcium and vitamin D (11,12) seems to have a protective effect on CRC risk and coffee intake (13)(14)(15) a conflicting effect, while frequent meals (16,17) and systematic physical activity (18,19) probably have modest protective effect. Added table salt or salted foods have been highly correlated with gastric cancer, but not with CRC.…”
mentioning
confidence: 99%
“…In addition, the association between coffee drinking and risk of cardiovascular disease remains inconclusive [15,[17][18][19][20][21][22][23]. The reason for the controversial results remains unclear.…”
Section: Discussionmentioning
confidence: 99%
“…Drinking coffee is associated with lower risks of metabolic syndrome, diabetes, and coronary heart disease [15][16][17][18][19]. However, there have been conflicting results regarding the association between coffee drinking and risk of cardiovascular disease [19][20][21][22][23]. The effect of coffee on endothelial function is also controversial [24][25][26][27].…”
Section: Introductionmentioning
confidence: 99%